2020
DOI: 10.1186/s12986-020-00464-w
|View full text |Cite
|
Sign up to set email alerts
|

Early life high-fat diet exposure evokes normal weight obesity

Abstract: Obesity is becoming one of the most severe global health problems. However, risk of developing normal weight obesity, where an individual has a high percentage of body fat despite a normal body mass index, is gaining attention since such individuals also develop systemic inflammation and metabolic dysregulation. In this study, juvenile (3-week-old) and adult (8-week-old) rats were fed a high fat diet (HFD) for 9 weeks and compared them with normal chow diet (NCD) fed rats. The HFD fed adult group showed increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…These results indicated that feeding an HFD causes overweight/obesity along with a greater body fat accumulation. Similar to the present work results, Maejima et al ( Maejima, Yokota, Horita, & Shimomura, 2020 ) found greater body weights and greater visceral and subcutaneous fat accumulation (30 vs 18% total body fat) in adult rats fed an HFD compared with adult rats fed a regular chow diet. Being parallel with the result of the present work, although not statistically significant, in terms of dietary mineral supplementation, supplementing 90 mg/kg zinc to the diet of mice was also shown to reduce body fat with reduced diameter and area of adipocytes ( Qi et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that feeding an HFD causes overweight/obesity along with a greater body fat accumulation. Similar to the present work results, Maejima et al ( Maejima, Yokota, Horita, & Shimomura, 2020 ) found greater body weights and greater visceral and subcutaneous fat accumulation (30 vs 18% total body fat) in adult rats fed an HFD compared with adult rats fed a regular chow diet. Being parallel with the result of the present work, although not statistically significant, in terms of dietary mineral supplementation, supplementing 90 mg/kg zinc to the diet of mice was also shown to reduce body fat with reduced diameter and area of adipocytes ( Qi et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…Feeding a high-fat diet (HFD) results in increased body weight and fat accumulation ( Maejima, Yokota, Horita, & Shimomura, 2020 ), which eventually leads to metabolic disorders such as obesity and diabetes ( Kebede and Attie, 2014 , Vernon et al, 2011 ). Treatment of such metabolic disorders requires altering lifestyle changes, including dietary advice and exercise.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we compare the beneficial effects of live and pasteurized A. muciniphila against metabolic disorder and associated inflammation, as well as gutbarrier function, using HFD-fed mice as a model. Consumption of a HFD triggers the onset and development of obesity, which is manifested by an increase in body weight, total fat, visceral fat and subcutaneous fat [43], in keeping with our results. We also observed significantly higher levels of adipose tissue gene expression of the lipogenic markers, ACC, C/EBPα and SREBP-1c in the HFD group than in the normal group.…”
Section: Discussionsupporting
confidence: 92%
“…Ample (pre)clinical studies point out a role for obesity in low-grade inflammation, detailed immune response, and the development of non-communicable diseases (for recent reviews see: [42,43]). Though unhealthy food consumption and overconsumption-induced obesity, even normal weight obesity, are suggested to be the major contributor to the increased prevalence of non-communicable diseases, other more complex societal factors might also be involved [44,45].…”
Section: Sustainable Immune Resiliencementioning
confidence: 99%